Effects and safety of Ginkgo biloba on depression: a systematic review and meta-analysis - Lin, Jingya; Sun, Xiaojing; Yang, Lingli (Frontiers in Pharmacology, 2024)
Background: Because depression is a major factor contributing to the global disease burden, we tried to analyze the effects and safety of Ginkgo biloba (GKB) on patients with depression. Methods: We conducted a literature search for articles published between January 2002 and May 2022 in seven online databases (PubMed, Scopus, Embase, Google Scholar, Web of Sciences, Cochrane Library, and China National Knowledge Infrastructure). A systematic literature review and meta-analysis were performed to compare the effects and safety of GKB on patients with depression, including subjective and objective indicators of depression evaluation. Results: In total, 21 eligible articles with nine indicators among 2074 patients were included. Several outcomes showed a difference, and the GKB group had better results than the control group, including the Hamilton Depression Scale (HAMD), after taking GKB for 4 weeks (MD = −2.86, 95%CI [−4.27, −1.46], p < 0.01), 6 weeks (mean difference (MD) = −3.36, 95%CI [−4.05, −2.67], p < 0.01), and 8 weeks (MD = −4.58, 95% CI [−6.11, −3.05], p < 0.01), modified Barthel index (MBI) (MD = 14.86, 95%CI [12.07, 17.64], p < 0.01), modified Edinburgh-Scandinavian stroke scale (MESSS) (MD = −4.57, 95%CI [−6.34, −2.79], p < 0.01), brain-derived neurotrophic factor (BDNF) (MD = 16.35, 95%CI [7.34, 25.36], p < 0.01), 5-hydroxytryptamine (5-HT) (MD = 4.57, 95%CI [3.08, 6.05], p < 0.01), and clinical efficacy (risk ratio, RR = 1.24, 95%CI [1.17, 1.32], p < 0.01). However, there were no differences in adverse events between GKB and controls. Conclusion: In conclusion, the main finding was that patients treated with GKB had better MBI, MESSS, BDNF, 5-HT, and HAMD values after 4 weeks, 6 weeks, and 8 weeks than the control group. GKB might reduce the risk of depression or depressive symptoms with safe clinical efficacy. Systematic Review Registration: identifier (INPLASY2023100052)